Implementasi Human Relations Dalam Membangun Etos Kerja Karyawan PT Federal International Finance - Cindy Meilany Putri; Lilik Sumarni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research was conducted to analyze the implementation of human relations at PT Federal International Finance. The approach in this study is qualitative with data collection techniques of interviews, observation and documentation. The purpose of this study was to determine the implementation of human relations at PT Federal International Finance and to find out the obstacles in developing the implementation of human relations at PT Federal International Finance. This research refers to Effendy's implementation theory (2020), which has five dimensions. The first is communication which aims to build cooperation within the company. The second is directives to tell the tasks that must be carried out by employees so that employees can find out what the instructions from the leadership are. The third is openness to build harmonization between leaders and employees for the sake of creating openness so that there is no social jealousy. The fourth is mutual respect with the aim that employees and leaders can respect each other. The fifth is loyalty, the important role of a company is having employees who are able to survive in any condition for the sake of building a company. The inhibiting factor for the implementation of human relations is the lack of smooth communication between leaders and employees. In addition, there are barriers to direction, openness, mutual respect, and loyalty which hamper the implementation of human relations.